Neural stem cells derived from the developing forebrain of YAC128 mice exhibit pathological features of Huntington's disease. (31st August 2020) - Li, Endan; Park, Hee Ra; Hong, Chang Pyo; Kim, Younghoon; Choi, Jiwoo; Lee, Suji; Park, Hyun Jung; Lee, Bomi; Kim, Tae Aug; Kim, Seong Jin; Kim, Hyun Sook; Song, Jihwan
Abstract: Objectives: Huntington's disease (HD) is a devastating neurodegenerative disease caused by polyglutamine (polyQ) expansion in the huntingtin (HTT) gene. Mutant huntingtin (mHTT) is the main cause of HD and is associated with impaired mitochondrial dynamics, ubiquitin‐proteasome system and autophagy, as well as tauopathy. In this study, we aimed to establish a new neural stem cell line for HD studies. Materials and methods: YAC128 mice are a yeast artificial chromosome (YAC)‐based transgenic mouse model of HD. These mice express a full‐length human mutant HTT gene with 128 CAG repeats and exhibit various pathophysiological features of HD. In this study, we isolated a new neural stem cell line from the forebrains of YAC128 mouse embryos (E12.5) and analysed its characteristics using cellular and biochemical methods. Results: Compared to wild‐type (WT) NSCs, the YAC128 NSC line exhibited greater proliferation and migration capacity. In addition to mHTT expression, increased intracellular Ca 2+ levels and dysfunctional mitochondrial membrane potential were observed in the YAC128 NSCs. YAC128 NSCs had defects in mitochondrial dynamics, including a deficit in mitochondrial axonal transport and unbalanced fusion and fission processes. YAC128 NSCs also displayed decreased voltage response variability and Na + current amplitude. Additionally, the ubiquitin‐proteasome and autophagy systems were impaired in the YAC128 NSCs. Conclusions: We have established a new neural stem line from YAC128 transgenic mice, which may serve as a useful resource for studying HD pathogenesis and drug screening. Abstract : The YAC128 NSC, a new neural stem cell line derived from the developing forebrain of YAC128 mice, exhibits pathological features of Huntington's disease, including mHTT aggregation, defective ubiquitin and autophagy systems and impaired axonal transport of mitochondria, which can serve as a useful resource for studying HD pathogenesis and drug screening